Purification and Characterization of the Recombinant Chitinase ChiBlUV02 of Bacillus licheniformis UV01 with a Choleoptericidal Effect on Hive Beetle (Aethina tumida) - Deny de Jesús Velasco-Vique; Argel Flores-Primo; Sóstenes Rodríguez-Dehaibes; María Guadalupe Sánchez-Otero; Violeta T. Pardío-Sedas; Rosa María Oliart-Ros; Gabriela Blasco-López; Rodolfo Quintana-Castro (Applied Microbiology)
The biotechnological applications of chitinases are diverse. They are used in industrial sectors such as pharmaceuticals, textiles, and agriculture, including the use of recombinant chitinases for pest control, since traditional treatments affect and contaminate hive products. Bacillus licheniformis UV01 bacterium is of interest, as it expresses genes for different enzymes, including chitinase. The Chibluv01 gene was cloned into the pHTP8 vector with a His/tag for purification using affinity chromatography. It showed a specific activity of 115 U/m. The optimal pH and temperature were 7.5 and 42 °C, respectively. The choleoptericidal activity (ability to kill beetles) of the enzyme was evaluated in the larvae and adult beetles of Aethina tumida treated with immersion in a purified enzyme extract at different concentrations, and the mortality was verified at 24, 48, and 72 h. Within 24 h of application, the mortality increased by 50% in the larval stage and 56.6% in adult beetles compared to the control groups. The LC50 and LC90 were obtained: 104.05 U/mL and 234.36 U/mL in larvae and 92.99 U/mL and 211.14 U/mL in adults, respectively. These results indicate the potential of the application of ChiBlUV02 chitinase in pest control.